Caudal block analgesia for paediatric infra-umbilical surgery: A prospective observational study - Gautam, Binod; Karki, Manan (Journal of Kathmandu Medical College, 2020)
Background: Caudal block is the most common regional anaesthesia technique used in children. It offers excellent perioperative analgesia in infra-umbilical surgeries. However, large-scale studies on caudal block in our paediatric population are not available.Objectives: We aimed to evaluate practice pattern, efficacy and safety of caudal block in paediatric infra-umbilical surgery.Methodology: Children (age less than 14 years) undergoing elective infra-umbilical surgery under general anaesthesia were included in this prospective observational study conducted over two years. Demographic characteristics, type of surgery, anaesthetic techniques and agents used, and details of caudal block were recorded. Perioperative events, complications and duration of analgesia were studied. Eligible children not receiving caudal block served as the control group. Analysis was performed using IBM Statistical Package for the Social Sciences version 20.Results: Caudal block was employed in 72 out of 183 children who completed the study. It was mostly preferred for children weighing less than 20 kilograms. Ketamine pre-medication was used in 123 children. Majority received Propofol induction and laryngeal mask. Halothane was preferred over Isoflurane for anaesthesia maintenance. Bupivacaine was the exclusively used local anaesthetic agent. Vascular puncture occurred in three children but no serious complication was observed. Need for supplement intraoperative analgesics was significantly lower, and duration of analgesia was significantly longer in caudal group. Intraoperative hypotension, laryngospasm during emergence and postoperative vomiting were the most frequent perioperative events.Conclusion: Pre-incisional single-shot caudal block is safe, effective and well accepted component of multi-modal perioperative analgesic regimen for younger children undergoing infra-umbilical surgery.